Pyoderma Gangrenosum Mimicking Necrotizing Fasciitis in a Marathon Runner With Myelodysplastic Syndrome - Samik Doshi; Yuna Lee (Annals of Internal Medicine: Clinical Cases)
A 62-year-old man with myelodysplastic syndrome presented with fever, leukocytosis, and a violaceous lesion on his right leg. His skin lesion worsened, and his fever persisted despite him receiving broad-spectrum antibiotics and multiple surgical debridements for a presumptive diagnosis of necrotizing fasciitis. Through careful review of histopathologic findings and his clinical presentation, he was subsequently diagnosed with pyoderma gangrenosum (PG). This case highlights an important diagnostic challenge. PG should be suspected in cases of nonresolving soft-tissue infection, particularly in the context of associated systemic disease, negative microbiological results, and negative work-up for autoimmune and malignant conditions.